2016
DOI: 10.1002/2015jd024537
|View full text |Cite
|
Sign up to set email alerts
|

Insights into riming and aggregation processes as revealed by aircraft, radar, and disdrometer observations for a 27 April 2011 widespread precipitation event

Abstract: This study presents aircraft spiral ascent and descent observations intercepting a transition to riming processes during widespread stratiform precipitation. The sequence is documented using collocated scanning and profiling radar, including longer-wavelength dual polarization measurements and shorter-wavelength Doppler spectra. Riming regions are supported using aircraft measurements recording elevated liquid water concentrations, spherical particle shapes, and saturation with respect to water. Profiling clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 64 publications
5
41
0
Order By: Relevance
“…Figure shows that the disdrometer time series is consistent with the 95th percentile time series, although differences are expected due to the different areas covered by each instrument, and besides, the total precipitation from the disdrometer is always larger than that measured by radar and a rain gauge because large droplets were not filtered as suggested by Giangrande et al . ().…”
Section: Data Collection Design and Processing Methodsmentioning
confidence: 98%
“…Figure shows that the disdrometer time series is consistent with the 95th percentile time series, although differences are expected due to the different areas covered by each instrument, and besides, the total precipitation from the disdrometer is always larger than that measured by radar and a rain gauge because large droplets were not filtered as suggested by Giangrande et al . ().…”
Section: Data Collection Design and Processing Methodsmentioning
confidence: 98%
“…Schrom et al () suggested a polarimetric technique to separate contributions from aggregates and dendrites in the DGL of midlatitude winter storms. Polarimetric signatures of the secondary ice mixed with aggregated and rimed snow in layers with temperature around −5°C were found by cloud and precipitation radar measurements in high‐latitude deeper snow clouds (Oue, Kumjian, Lu, Verlinde, et al, ; Sinclair et al, ), midlatitude mesoscale convective systems (Giangrande, Toto, Bansemer, et al, ; Kumjian et al, ), and midlatitude snowstorms (Kumjian & Lombardo, ). However, combining polarimetric measurements with the analysis of Doppler spectra yields a much better chance to identify and separate different types of ice, and to quantify their amounts if their corresponding fall velocities are associated with separate peaks in the Doppler spectrum.…”
Section: Introductionmentioning
confidence: 96%
“…Dual‐polarization radar observations are often used to identify ice precipitation regions affected by riming [e.g., Straka et al , ; Liu and Chandrasekar , ; Chandrasekar et al , ; Giangrande et al , ]. Accurate identification of such regions would improve our understanding of precipitation processes as well as improve aviation safety [ Ellis et al , ], among other applications.…”
Section: Introductionmentioning
confidence: 99%